2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5334510
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intraventricular blood using EIT in a neonatal piglet model

Abstract: We have developed a sensitive EIT protocol for detection of intraventricular bleeding. A common model of human neonates is the neonatal piglet. We used our method to test the sensitivity of our method and device to small amounts of blood-like fluid injected near the left and right ventricles of a piglet cadaver. Comparing blood-like fluid detection in open an closed piglet skulls, we found that we could detect amounts of blood less than 0.5 ml, which is smaller than that required for our target of detecting gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…While several other EIT research groups have explored the effects of intraperitoneal and intracranial hemorrhage, 22,23,24 to the best of our knowledge, the novel EIT implementation described in this manuscript is at present the only study to show in-vivo , real-time, tomographic reconstructions of mass-effect, hemorrhage, and cessation of blood flow. Wang et.…”
Section: Discussionmentioning
confidence: 99%
“…While several other EIT research groups have explored the effects of intraperitoneal and intracranial hemorrhage, 22,23,24 to the best of our knowledge, the novel EIT implementation described in this manuscript is at present the only study to show in-vivo , real-time, tomographic reconstructions of mass-effect, hemorrhage, and cessation of blood flow. Wang et.…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers (Sadleir and Tang 2009, Sadleir et al 2009, Tang et al 2010, Tang and Sadleir 2010, 2011) we described promising results in numerical simulations and phantom experiments. We found that an 16-electrode layout based on the electroencephalograph (EEG) 10–20 layout, combined with a measurement strategy that involved applying a sequence of current patterns with all return paths over the anterior fontanel (the ‘Cz pattern’) was superior to other patterns considered.…”
Section: Introductionmentioning
confidence: 82%
“…Xu et al, Manwaring et al, Dowrick et al, Sadleir et al, and Dai et al established different animal models of intracranial hemorrhage (ICH), including intraparenchymal hemorrhage (IPH), subarachnoid hemorrhage (SAH) and intraventricular hemorrhage (IVH). They found that EIT could accurately reflect the real-time impedance change caused by ICH, even though the blood volume was much smaller than that of the brain, as in the case of the IPH pig model with 5 ml blood injection [30][31][32][33][34]. Moreover, Shuai et al explored the ability of EIT to monitor intraperitoneal hemorrhage in a pig model and observed that the intraperitoneal blood volume changes could be continuously identified by the observation of EIT images throughout the bleeding progression [35].…”
Section: Introductionmentioning
confidence: 99%